Exploring color workshop with new exercises, lessons and demonstrations - Leland, Nita (North Light Books, 2016)
Finding color combinations that not only work but excite the eye is one of the greatest challenges artists face. This updated and expanded 30th anniversary edition of the North Light classic Exploring Color teaches artists of all mediums and skill levels how to use and control color in their artwork and shows how exhilarating and enjoyable the ride can be. Popular art instructor and best-selling author Nita Leland will help you take any artwork you make to new color heights. Memorable paintings from more than 30 contributing artists are inside towill inspire you, along with 75+ hands-on exercises, 8 step-by-step demonstrations and countless nuggets of color knowledge--all in your own private workshop! Learn how to master color mixing, assemble the perfect palette for your artistic goals, select just the right color scheme, and communicate color in a way that elevates your designs way beyond the ordinary. Start a handy journal to keep track of your discoveries, with customized mixtures, color wheels, reference charts and other tools designed to uncover your color personality and help you work with color more efficiently. Nita knows that the quest for perfect color can be fun, and it can be yours. So stop guessing, and start exploring!